The Design of Warehouse Data Structure to Support Product Marketing Plan Using Star Schema - Dewi Kania Widyawati (Politeknik Negeri Lampung, 2012)
Warehouse data is a database form that has high capacity data and is not operational. Warehouse data structure of product marketing is developed using star schema so that it can fulfil the need of product marketing information with a variety of dimension criteria. The data recorded into product marketing warehouse data is extracted from the data in operational database. By implementing this warehouse data, company leader will be able to evaluate and plan products easily based on specific marketing regions and evaluate the performance of agent who becomes his/her partner. In order that the data in product marketing warehouse data can be accessed easily, it is necessary to develop a special application and the warehouse data structure needs to be developed continuously so that it becomes more comprehensive.Â Keywords: database, warehouse data, star schema.